Analysis of the Regulatory and Legal Framework of the Socio-Economic Development in the Far North Regions of Russia - RYTOVA, Elena V.; KOZLOV, Aleksandr V.; GUTMAN, Svetlana S.; ZAYCHENKO, Irina M. (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The paper studies the regulations of the socio-economic development in the Russian Far North. This work presents the research of the main historical stages of the law formation and the analysis of the existing regulations of the socio-economic development in the Far North. It was found out that the Far North economic and social status has deteriorated in recent years due to the introduction of novel legislations. The analysis of laws has also shown the reorientation of the state towards the strong support of only a part of the Far North territories, namely its Arctic region. Thus, some proposals have been formulated to improve the regulations of the socio-economic development of the Far North in order to solve urgent social and economic problems of the region.